DAMPAK TELEMEDIS TERHADAP AKSES PELAYANAN KESEHATAN DI MASYARAKAT PEDESAAN - Nora Lelyana (Tahta Media Group, 2024)
Telemedicine has emerged as a pivotal solution for addressing healthcare disparities in rural communities, where access to medical services is often limited. This study aims to evaluate the impact of telemedicine on healthcare access in rural areas, focusing on how residents perceive and utilize telemedicine, the effect on healthcare outcomes, and the barriers to its implementation. Using qualitative research methods, secondary data were collected from academic journal articles, government reports, and healthcare surveys. Findings reveal that rural residents generally perceive telemedicine positively, appreciating its convenience and accessibility, although technological literacy and trust in technology remain concerns. The impact on healthcare outcomes is significant, with improvements noted in chronic disease management, patient satisfaction, and cost savings. However, several barriers impede the widespread adoption of telemedicine, including technological infrastructure limitations, regulatory complexities, reimbursement issues, and the need for provider and patient education. The study concludes that while telemedicine has the potential to transform rural healthcare, addressing these barriers is crucial for optimizing its effectiveness and sustainability.